2021
DOI: 10.1155/2021/6674965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Fat Diet  on  the Intestinal Flora in Letrozole-Induced Polycystic Ovary Syndrome Rats

Abstract: Aim. The aim of this study was to explore whether letrozole and high-fat diets (HFD) can induce obese insulin-resistant polycystic ovary syndrome (PCOS) with intestinal flora dysbiosis in a rat model. We compared the changes in the intestinal flora of letrozole-induced rats fed with HFD or normal chow, to explore the effects of HFD and letrozole independently and synergistically on the intestinal flora. Methods. Five-week-old female Sprague Dawley (SD) rats were divided into four groups: control (C) group fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have shown that Akkermansia can reduce the body weight and total cholesterol of obese patients, increase insulin sensitivity, improve IR, and reduce inflammatory reaction ( Shin et al., 2014 ; Dao et al., 2016 ; Depommier et al., 2019 ), and its mechanism may be adjusting the thickness of intestinal mucosa and maintaining the integrity of intestinal barrier ( Derrien et al., 2004 ). As a potential probiotic, Blautia was significantly enriched in the treatment group, and it was proved to play certain roles in metabolic diseases, inflammatory diseases, and biotransformation ( Eren et al., 2015 ; Liu et al., 2021 ; Zheng et al., 2021 ). Meanwhile, Clostridium_sensu_stricto_1 , which was thought to cause inflammation and lead to severe intestinal infections ( Fletcher et al., 2021 ), was significantly higher in the model group and significantly lower in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Akkermansia can reduce the body weight and total cholesterol of obese patients, increase insulin sensitivity, improve IR, and reduce inflammatory reaction ( Shin et al., 2014 ; Dao et al., 2016 ; Depommier et al., 2019 ), and its mechanism may be adjusting the thickness of intestinal mucosa and maintaining the integrity of intestinal barrier ( Derrien et al., 2004 ). As a potential probiotic, Blautia was significantly enriched in the treatment group, and it was proved to play certain roles in metabolic diseases, inflammatory diseases, and biotransformation ( Eren et al., 2015 ; Liu et al., 2021 ; Zheng et al., 2021 ). Meanwhile, Clostridium_sensu_stricto_1 , which was thought to cause inflammation and lead to severe intestinal infections ( Fletcher et al., 2021 ), was significantly higher in the model group and significantly lower in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) also found that α-diversity in PCOS-IR model rats had an increasing trend. As we all know, diet is one of the most important environmental factors that change the structure of the microbiota ( David et al., 2014 ; Zheng et al., 2021 ). Whether the increase in α-diversity was caused by a high-fat diet or a rising proportion of harmful bacteria needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations in this study that need to be explored. First, studies have found that inflammatory reaction is significantly correlated with the occurrence and development of PCOS [ 27 , 28 ]. This study did not analyze the inflammatory indicators of the subjects, so the relationship between miR-363-3p and inflammation cannot be verified for the time being.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous patients with PCOS have bad habits, such as an adoration of sweets, a love of fat, an absence of dietary fiber, and little exercise, which affects gut health ( 18 , 78 ). A high-fat diet (HFD) was linked to an increase in the pro-inflammatory microbiota, such as Clostridiales , Bacteroides , and Enterobacteriales , and a decrease in the anti-inflammatory microbiota, such as Lactobacillus , in the rat ( 75 ).…”
Section: Crosstalk Between Pcos and Gut Metabolitesmentioning
confidence: 99%
“…Interestingly, the activity and contents of gut metabolites can be regulated by the gut microbiota ( 18 , 19 ). The correlations between gut metabolites and gut microbiota have been demonstrated in numerous metabolic diseases, such as obesity, type 2 diabetes, NAFLD, and cardiovascular diseases ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%